Modified GaussNewton Algorithm for Evaluation of Full Lightning Impulse Voltage Parameters - Panuwat Jamroen; Poom Yoosorn; Suthasinee Waengsothorn; Peerawut Yutthagowith (My University, 2021)
This paper presents an efficient curve fitting technique based on a Gauss-Newton (GN) method with a varied damping factor for the evaluation of lightning impulse voltage parameters.The proposed method can be used to determine the base curves of full lightning impulse voltages with oscillations corrected from the parameters of test cases according to the standard (IEC 61083-2).To verify the performance of the proposed method, base curves reconstructed from the developed method were compared with curves reconstructed from nonlinear least squares regression using the Levenberg-Marquardt (LM) algorithm, as prescribed in the standard.The proposed method provides the same results as the standard recommended method but its execution time is significantly shorter.The results of this study indicate that the proposed method is suitable for evaluating lightning impulse voltage parameters.
Keywords: Impulse generator; Power Quality and Harmonics